Pengaruh Ulasan Pelanggan Online dan Siaran Langsung Serta Persepsi Nilai Terhadap Minat Beli Tas Bostanten Pada E-Commerce Shopee - Riska Resti Fauzi; Doddy Adhimursandi (Universitas Katolik Soegijapranata, Semarang, 2026)
This study aims to analyze the effect of online customer reviews, live streaming, and perceived value on purchase intention of Bostanten bags on the Shopee e-commerce platform. This research employs a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 112 respondents who are Shopee users and familiar with Bostanten bag products. The sampling technique used was purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach utilizing SmartPLS software.The results indicate that online customer reviews have a positive but not significant effect on purchase intention. Meanwhile, live streaming and perceived value have a positive and significant effect on purchase intention of Bostanten bags on Shopee. These findings suggest that interactivity during live streaming and consumers’ perceived value regarding product quality and benefits play a crucial role in increasing purchase intention. This study provides practical implications for companies in developing effective digital marketing strategies within e-commerce platforms.